Assessment of Entrepreneurial Skills Acquired by University STEM Education Graduands for Sustainable Development in Nigeria - Izunna S. NWUBA; Sussan O. EGWU; Maxwell C. OBIKEZIE; Chisom P. ANYIGOR; Joy A. EKE; Stella O. ANAZODO (Journal of Management and Science, 2025)
The drive to produce graduates who can adapt and thrive in an economy dwindling society necessitated the investigation on entrepreneurial skills (ES) acquired by STEM education graduands for sustainable development in Anambra State, adopting a descriptive survey research design. 245 graduating students of the Department of Science Education, Nnamdi Azikiwe University, Awka enrolled in the 2024/2025 academic session, constituted the population. Taro Yamane’s formula was employed to estimate a sample of 152 respondents, drawn using simple random sampling technique. An adapted instrument titled “Entrepreneurial Skills Questionnaire for Sustainable Development (ESQSD)” was employed to collect data. The questionnaire face validated by three experts and subjected to pilot testing, yielded a reliability coefficient of 0.74 by Cronbach Alpha estimation. Frequency counts, percentages, mean and standard deviation were employed to answer the research questions and ANOVA for the null hypotheses. The findings revealed that the respondents agreed that, out of the 25 identified ES, 24 of them are needed by them. Sadly, out of the 24 agreed needed skills, they possessed only 17, identifying rigid curriculum, poor learning environment among others as some major challenges hindering the acquisition of ES in the university. The hypotheses tested further confirms that no significant difference existed between the skills identified as needed by STEM graduands as well those agreed as possessed by them. Considering the findings, it was recommended among others that education stakeholders of higher institutions should restructure the university STEM curricula to incorporate activities that will foster students’ acquisition of ES, while in school.